Pengaruh Motivasi Kerja, Disiplin Kerja, Dan Fasilitas Kerja Terhadap Kinerja Karyawan Royal Property Batam - , Yohanes Bio Siga; Sanga , Laurensius Dihe; Harianja , Josepin (Tractare: Jurnal Ekonomi-Manajemen, 2025)
This study examines the influence of work motivation, work discipline, and work facilities on employee performance at Royal Property Batam. Property companies like Royal Property Batam require quality human resources (HR) to improve company performance. Employee performance is a crucial factor in achieving organizational goals, including productivity and efficiency. The method used in this study is quantitative. Quantitative methods are the systematic and objective collection, processing, analysis, and presentation of data to solve a problem or test a hypothesis to develop general principles.The data collection technique used a questionnaire distributed through Google Forms. Data analysis using SPSS Version 26 research results found that the t-value of Work Motivation was 3.730> ttable value of 2.76 with a significance level of 0.000 <0.05 then Ho was rejected and Ha was accepted. The Work Discipline variable that the t-value of Work Discipline was 7.900> from ttable 2.76 with a significance value of 0.000 <0.05 then Ho was rejected and Ha was accepted, the Work Facilities variable that the t-value of Work Facilities was 0.020 <ttable 2.76 with a significance value of 0.984> 0.05 then Ho was accepted and Ha was rejected, the Work Discipline and Work Facilities variables showed that the Fvalue of the independent variables Work Motivation, Work Discipline and Work Facilities was 118.890 with a significance level of 0.000. The significance value is less than 0.05, and F count 118.890 > 2.76, so H0 is rejected and Ha is accepted. This means that work motivation, work discipline, and work facilities simultaneously have a positive and significant influence on the performance of Royal Properti Batam employees.